Thermally tunable ultra-thin metamaterial absorber at P band. Issue 11 (24th July 2019) - Wang, Liansheng; Xia, Dongyan; Fu, Quanhong; Wang, Yuan; Ding, Xueyong; Yang, Bo
Abstract : We report a new kind of ultra-thin tunable metamaterial absorber at P band based on the high permittivity and its thermally tunable property of strontium titanate. It is composed of a copper ring and strontium titanate at the top layer, FR4 and copper film at the middle and bottom sections. The absorption of metamaterial absorber reaches 96% at 684 MHz at 300 K and acquires the tunable property of absorption frequency by altering its external temperature. Moreover, we study the surface current and electric field distribution of the metamaterial absorber at 684 MHz at 300 K to explore the physical mechanism of electromagnetic wave absorption. Finally, we prove that the absorption is insensitive to the polarization due to the rotational symmetry of the unit cell, but sensitive to the incident angle and structure size. Our study opens a new prospect in designing the ultra-thin metamaterial absorber at P band.